Nutritional interventions and cognitive-related outcomes in patients with late-life cognitive disorders: A systematic review - Solfrizzi, Vincenzo; Agosti, Pasquale; Lozupone, Madia; Custodero, Carlo; Schilardi, Andrea; Valiani, Vincenzo; Santamato, Andrea; Sardone, Rodolfo; Dibello, Vittorio; Di Lena, Luca; Stallone, Roberta; Ranieri, Maurizio; et al. (Neuroscience and biobehavioral reviews, 2018)
•Medical food approach improved cognitive biomarkers without clear effects in mild Alzheimer’s disease (AD) and mild cognitive impairment (MCI).•Antioxidant-rich food supplementations improved specific cognitive outcomes in MCI and mild-to-moderate dementia, but only in small samples.•Supplementation with n-3 polyunsaturated fatty acids (PUFA) improved specific cognitive domains and cognitive-related biomarkers in MCI and AD.•Antioxidant vitamin and trace element improved only cognitive-related outcomes and biomarkers, without effect on cognition in AD and MCI.•High-dose B vitamin supplementation in AD and MCI improved cognitive outcomes but only in the subjects with a high baseline plasma n-3 PUFA. There have been a large number of observational studies on the impact of nutrition on neuroprotection, however, there was a lack of evidence from randomized clinical trials (RCTs). In the present systematic review, from the 32 included RCTs published in the last four years (2014–2017) in patients aged 60 years and older with different late-life cognitive disorders, nutritional intervention through medical food/nutraceutical supplementation and multidomain approach improved magnetic resonance imaging findings and other cognitive-related biomarkers, but without clear effect on cognition in mild Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Antioxidant-rich foods (nuts, grapes, cherries) and fatty acid supplementation, mainly n-3 polyunsaturated fatty acids (PUFA), improved specific cognitive domains and cognitive-related outcomes in MCI, mild-to-moderate dementia, and AD. Antioxidant vitamin and trace element supplementations improved only cognitive-related outcomes and biomarkers, high-dose B vitamin supplementation in AD and MCI patients improved cognitive outcomes in the subjects with a high baseline plasma n-3 PUFA, while folic acid supplementation had positive impact on specific cognitive domains in those with high homocysteine.